Start cleaning, stop infecting : a communication campaign to promote proper hand hygiene practices among hospital visitors - Gn, Ashley (2018)
This paper presents ‘Start Cleaning, Stop Infecting’, a communication campaign to educate visitors in Singapore General Hospital (SGH) on proper hand hygiene practices, initiated by four final-year students from Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign aims to improve hand hygiene compliance rate among hospital visitors, by having adults aged 18 and above to be aware of when and how they should clean their hands in a hospital setting. Through a literature review and formative research, the team was able to discover that the majority of visitors cleaned their hands after visiting a patient with the intention of protecting themselves, among other findings. In contrast, much fewer visitors reported that they clean their hands before visiting a patient – a major concern when touch remains the most common transmitter of diseases. Building on these findings, a three-phase campaign approach was designed as a guide for the campaign’s execution. The campaign strategy, which combines interactivity and education, promotes hand hygiene in an engaging and memorable way for 5,390 hospital visitors over the course of six weeks. Limitations and challenges of the campaign were also discussed to provide useful learning insights for future campaigns. Finally, survey results, photos, correspondences, and collaterals that were used in the campaign execution can be found in the appendices of this paper.